2016
DOI: 10.1016/j.foreco.2016.04.054
|View full text |Cite
|
Sign up to set email alerts
|

Geometrid moth assemblages reflect high conservation value of naturally regenerated secondary forests in temperate China

Abstract: The widespread destruction of mature forests in China has led to massive ecological degradation, counteracted in recent decades by substantial efforts to promote forest plantations and protect secondary forest ecosystems. The value of the resulting forests for biodiversity conservation is widely unknown, particularly in relation to highly diverse invertebrate taxa that fulfil important ecosystem services. We aimed to address this knowledge gap, establishing the conservation value of secondary forests on Dongli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 67 publications
3
5
0
Order By: Relevance
“…On the contrary, we found the lowest dissimilarity in mature forests. Such results are in line with previous studies of both geometrid moths and carabid beetles in one of our study areas, at Donglingshan, where species dissimilarity was higher than in the mature forest at Changbaishan (Zou, Sang, Wang, et al, ; Zou et al, ). The relatively high dissimilarity in beetle assemblages within secondary and plantation forests suggests that they are not strongly dominated by generalists.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…On the contrary, we found the lowest dissimilarity in mature forests. Such results are in line with previous studies of both geometrid moths and carabid beetles in one of our study areas, at Donglingshan, where species dissimilarity was higher than in the mature forest at Changbaishan (Zou, Sang, Wang, et al, ; Zou et al, ). The relatively high dissimilarity in beetle assemblages within secondary and plantation forests suggests that they are not strongly dominated by generalists.…”
Section: Discussionsupporting
confidence: 93%
“…The difference could be related to plantation forests in Europe harbouring a much lower tree species richness than plantation forests in our study region. In fact, our results also correspond with patterns previously reported for geometrid moths in secondary and mature forests from two of our study areas, Changbaishan and Donglingshan, where recently established forests were shown to harbour similar levels of α‐diversity to mature forests (Zou et al, ). In addition, our results are in line with a recent study from south‐central China by Hua et al (), who reported general positive impacts of species‐rich mixed forests on regional biodiversity.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Due to cool and dry climate, the litter decomposes lowly, which results in deep litter and organic layers [ Yu et al , ]. In the area, oak ( Quercus liaotungensis Mayr) forest is the originally main forest type, but some areas are partly reforested with coniferous plantations of evergreen Chinese pine ( Chinese pine tabulaeformis ), larch ( Larix principis‐rupprechtii ), and mixed deciduous forest ( Betula platyphylla Suk, Carya cathayensis Sarg, Betula dahurica Pall, and Acer mono ) [ Zou et al , ]. Therefore, these four forest types were selected for the study: Chinese pine plantation, larch plantation, oak forest, and mixed deciduous broad‐leaved forest.…”
Section: Methodsmentioning
confidence: 99%